TOURISM AFTER CORONAVIRUS PANDEMIC - WAY FORWARD FOR TOURISM AND HOSPITALITY INDUSTRY IN THE UZBEKISTAN - Buribaeva, Mukhlisa (Educational Research in Universal Sciences, 2023)
A coronavirus infection was confirmed in China in January 2020. After two years of the pandemic, countries are still dealing with new virus variants, fifth and sixth waves differing degrees of success in vaccinating their national populations during two years. And this paper looks into research questions by comparing the effects of international travel on the private sector before and after COVID-19. The article recommended qualitative research methodologies as an analytical technique to gather information from workers in the tourism industry. Through online questionnaire surveys, the respondents’ opinions were gathered and also future traveler arrivals and people’s desire for particular tourist destinations has taken into account.